Locomotion Index and Retinal Thickness of the Eye Anguilla bicolor bicolor in its Developmental Stage - Nur Indah Septriani; Anita Restu Puji Raharjeng; Maria Nur Hasanah; Khoiruddin Anshori; Frida Prasetyo Utami (Biota, 2023)
When migrating to the deep sea, the eye of the eel which functions for locomotion will adapt to the deep environment. This study is the first study to identify the locomotion index and the retinal structure at the stage glass eel, elver, yellow, and silver eel Anguilla bicolor bicolor. Character and habitat information for each stage of eel can be used as a conservation strategy. Seventeen eel fish samples were collected from the Pasir Puncu River in Purworejo. Observation of the Locomotion Index is done by comparing the Eye Index (EI), Pectoral Fin Index (PFI), Anal Fin Index (AFI), and Dorsal Fin Index (DFI) at several stages of development of eel, while histologically the observations were carried out with analyzing the retina structure and the thickness of Rod and Cone Layer (RCL), Outer Nuclear Layer (ONL), Inner Nuclear Layer (INL), Ganglion Layer (GL) and Nerve Fiber Layer (NFL). Based on these observations it can be seen that the retina (RC, ONL, INL, GL, NFL) will have increased from yellow to the silver stage, this is due to adaptation eels that adapt to new habitats. The locomotion index shows that the more developed the pectoral fins, the greater the thickness of the NFL, which indicates the greater the number of nerves used for adaptation in the ocean. In the early elver stage, eels tend to swim on the surface of the water in brackish waters. At the yellow eel stage, the eels have started swimming on the bottom of the water that is rich in the substrate with darker environmental characteristics, while at the silver stage, the eel will begin to adjust to the darker deep sea.